Immigration and Swiss House Prices - Kathrin Degen; Andreas M. Fischer (Swiss Journal of Economics and Statistics, 2017)
This study examines the behavior of Swiss house prices in relation to immigration flows for 85 regions from 2001 to 2006. The results show that the nexus between immigration and house prices holds even in an environment of low house price inflation and modest immigration flows. An immigration inflow equal to 1 % of an area's population is coincident with an increase in prices for single-family homes of about 2 .7 %, a result consistent with previous studies. The overall immigration effect for single-family houses captures almost two-thirds of the total price increase.
Keywords: F22; J61; R21; 330; Immigration; housing prices